Judd Ofelt Analysis and Optical Properties of Rare Earth Doped Tellurite Glasses - Hong, Tran Thi; Dung, Phan Tien; Quang, Vu Xuan (Communications in Physics, 2014)
In this work, the structural characteristic and photoluminescence properties were investigated in Eu\(^3 + \) ions-doped B\(_2\)O\(_3\)-TeO\(_2\) –ZnO-Na\(_2\)O glasses. These glasses were prepared by the melting method in air, after that thermal annealed 350C, 450C and 550C for different times. The analysis results of structure on these glasses showed the formation of micro-crystals in host glass after thermal annealed process. The photoluminescence spectra of Eu\(^3 + \) ions in these samples were observed. The local vibration mode around Eu\(^3 + \) ions was investigated by the phonon side band associated with \(^7\)F\(_0\)- \(^5\)D\(_2\) transition of Eu\(^3 + \). Judd-Ofelt parameters have been evaluated from photoluminescence spectra and were to predict the luminescence intensity ratios of \(^5\)D\(_0 → ^7\)F\(_J\) (J=2, 4 and 6) to \(^5\)D\(_0 → ^7\)F\(_1\) transition. The obtained results have been used for calculating \(Ω_2\), \(Ω _4\), \(Ω _6\) parameters by using Judd-Ofelt theory. These \(Ω _2\), \(Ω _4\), \(Ω _6\) parameters allow to derive radiative properties of Eu\(^3 + \) ions in glass material such as transition probabilities, radiative lifetimes and peak stimulated emission cross-section for the \(^5\)D\(_0 → ^7\)F\(_J\) transitions